P 141 Cerebellar impacts on neural networks of emotional attention as evidenced by event related potentials. Issue 10 (October 2017) - Adamaszek, M.; Schuch, H.; Kessler, C.
Abstract : Background: The cerebellum is highly indicative to contributions to high-order functions of emotion, supporting responsible domains of cerebral neural networks in processing of distinct emotional cues. So the impact of the attentional modes of the cerebellum deems of particular interest for separating a selective pathway of emotionally driven cues, corresponding neurophysiological patterns in cerebellar disorders might provide further informations about the cerebellar role in emotional attention. Methods: Eight patients with a ischemic lesion of the cerebellum (five unilateral, three bilateral) and seven patients without stroke history were studied. Four neurophysiological paradigms were engaged along a confined set of the International Affective Picture System (IAPS) with neutral as well as emotional cues of different valence and arousal, each presented in a protocolled stream. Event-related Potentials (ERP) of early and late processing stages of selective and divided attention to stimulus processing were recorded by a 129 sensor array (Geodesic Inc.). Results: In opposite to control subjects, patients with a cerebellar lesion predominately of the posterior lobe showed a deviant early posterior negativity (EPN) at temporo-occipital locations in paradigms probing the divided attention to emotional arousing cues, whereby these effects were only significant for the acccording cognitive ERP (P200, P300). Patients with a cerebellar lesion in opposite to control subjects showed also a reduction of the Late Positive Potentials (LPP) at centro-parietal locations, whereby this observation was without a striking statistical significance rather due to the small sample size. Conclusions: Patients of cerebellar damage in our study disclosed neurophysiological patterns of impaired divided attention at the early stage and presumably also at forwarding stages of emotional processing. According to the findings of preserved selective attention to emotional cues as well as the indicative neurophysiologic patterns of enhanced cognitive activities mainly served by domains of the attentional and executive functions, compensatory guidance of the ventromedial and dorsolateral prefrontal cortex are highly warranted as crucial to ERP generation in our study sample. In respect to some restrictions of statistical output, application of the used paradigms to a greater study sample as well as a more in-depth analysis of the dipole sources should provide an increased precision of concerned regions of neural ERP generation.